A pilot study on cryopreservation of canine platelets - M. Ranjith Kumar; P. Selvaraj; S. Prathaban; G. Dhinakar Raj; V. Maroudam (Indian Journal of Veterinary and Animal Sciences Research, 2025)
Platelet transfusion is less commonly used in veterinary medicine, since the platelet products are not readily available. Cryopreservation of canine platelets may provide ready to use platelets. Towards this, a study was undertaken to assess cryopreservation of canine platelets for long term usage. Platelets were collected from healthy donors were then divided into three categories: fresh, cryopreserved in 6 percent Dimethyl Sulfoxide (DMSO) and cryopreserved in 6 percent Hydroxy Ethyl Starch (HES). After adding cryo-protectant to platelets, they were transferred to cryocyte containers and placed in a -80˚C freezer and stored. Assessment of the platelet count and recovery was carried out on 7 th and 14 th day of cryopreservation. Aerobic bacterial cultures from all tested platelet units yielded no growth. The use of DMSO as a cryo-protectant with a controlled cooling rate was found to be a simple, rapid and efficient method for canine platelet cryopreservation and provided a good recovery of platelets than the use of HES.